Kidney Transplantation: A Guide to the Care of Kidney Transplant Recipients - McKay, Dianne B.; Steinberg, Steven M.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Kidney Transplantation: A Guide to the Care of Kidney Transplant Recipients is an easy to read, up to date, clinical resource written by experts in the field of kidney transplantation. The book explains how donors and recipients are selected for transplantation, how the surgical procedure is performed, and how the experts recognize and treat rejection. This guide to the care of the kidney transplant recipient aims to provide practical guidelines for management of the post-transplant recipient and is targeted to community nephrologists and general internists who care for the patient with a kidney transplant. Dianne B. McKay, MD, is Associate Professor at The Scripps Research Institute, La Jolla, California. Steven M. Steinberg, MD, is affiliated with the Sharp Memorial Hospital, San Diego, California.
Ten Things Not to Do -- The Transplant Procedure: Surgical Techniques and Complications -- What Is Transplant Immunology and Why Are Allografts Rejected? -- What Is Histocompatibility Testing and How Is It Done? -- Kidney Allocation: Role of UNOS and OPOs -- Live Donors: How to Optimally Protect the Donor -- Laparoscopic Donor Nephrectomy: Essentials for the Nephrologist -- New Sources in Living Kidney Donation -- What Are Immunosuppressive Medications? How Do They Work? What Are Their Side Effects? -- Optimizing Immunosuppression -- Evaluation of Renal Allograft Dysfunction -- The Kidney Transplant Biopsy -- Evaluation of the Kidney Transplant Candidate and Follow-Up of the Listed Patient -- The Acute Care of the Transplant Recipient -- Post-transplant Cardiovascular Disease -- Diabetes Mellitus and Transplantation: Risks for Post-transplant Diabetes -- Infections in Kidney Transplant Recipients -- Malignancies Before and After Transplantation -- Bone Disease in Renal Transplantation -- Sexuality and Pregnancy Before and After Kidney Transplantation -- Socioeconomic Issues and the Transplant Recipient -- Adherence to the Immunosuppressive Regimen in Adult and Pediatric Kidney Transplant Recipients -- Transitioning Between Pediatric and Adult Clinics.
Keywords: Nephrology; Surgical transplantation; Internal medicine; Nephrology; Transplant Surgery; Internal Medicine